Bradycardia unresponded to atropin testing was successfully treated with therapeutic plasma exchange in a patient with severe COVID-19 complicated by Guillain-Barré syndrome: A case report - Duong-Quy, Sy; Huynh-Truong-Anh, Duc; Tran-Xuan, Quynh; Nguyen-Quang, Tien; Nguyen-Thi-Kim, Thanh; Nguyen-Chi, Thanh; Tran-Ngoc-Anh, Thuy; Nguyen-Van-Hoai, Nam; Do-Thi-Thu, Mai; Tang-Thi-Thao, Tram; Bui-Diem, Khue; Hoang-Anh, Tien; et al. (Frontiers in Cardiovascular Medicine, 2023)
SARS-COV2 (COVID-19) remains an emerging and alarming situation worldwide since the last two years. The symptoms of COVID-19 are not only localized in respiratory system but also expended in different organs. Bradycardia associated with Guillain-Barré Syndrome (GBS) is one of a rare complication of autonomic and peripheral neurological manifestation of COVID-19. In this case report, we present a young man aged 26 years-old, diagnosed with bradycardia associated with GBS after contracting COVID-19. This patient had firstly the typical symptoms of COVID-19 and was hospitalized in intensive care unit (ICU) for acute respiratory distress syndrome (ARDS). Then, he got the weakness in the lower extremities, diminished tendon reflexes, loss of sensation without sphincter muscle disorders and bradycardia. His bradycardia was not responded to atropine testing. The patient was treated concurrently with high flow nasal canular, systemic corticosteroid, anticoagulation and therapeutic plasma exchange (TPE) for COVID-19-induced ARDS, bradycardia and GBS. His ARDS and bradycardia were improved after the first cycle of TPE and medical treatment. After three cycles of TPE, the patient recovered progressively his muscle strength in the lower limbs and peripheral sensation disorders. He was discharged from the hospital in stable condition after 4weeks of hospitalization and followed-up during 6 months for the cardio-respiratory and neurological complications. In this case report, physicians might have the difficulties and crucial challenges in diagnosis and treatment of COVID-19 induced bradycardia and GBS during pandemic outbreak. However, the patient outcome seems to be optimistic with the treatment combining the conventional treatment associated with therapy plasma exchange.